Raltegravir (RAL) in Neonates: Dosing, Pharmacokinetics (PK), and Safety in HIV-1–Exposed Neonates at Risk of Infection (IMPAACT P1110). (1st May 2020) - Clarke, Diana F.; Acosta, Edward P.; Cababasay, Mae; Wang, Jiajia; Chain, Anne; Teppler, Hedy; Popson, Stephanie; Graham, Bobbie; Smith, Betsy; Hazra, Rohan; Calabrese, Kat; Bryson, Yvonne; et al.
Abstract : Background: Adequate pharmacokinetic and safety data in neonates are lacking for most antiretroviral agents. Raltegravir is a selective HIV-1 integrase strand transfer inhibitor available in a granule formulation suitable for use in neonates and young infants as prophylaxis or treatment of HIV infection. Methods: IMPAACT P1110 is a phase 1, multicenter, noncomparative dose-finding study of raltegravir in infants exposed to HIV-1 infection. A 2-cohort adaptive design was utilized where pharmacokinetic data from infants in cohort 1 who received 2 single doses of raltegravir 3 mg/kg were included in population modeling and simulations to guide selection of a daily dose for infants in cohort 2. Results: A total of 52 infants enrolled in IMPAACT 1110: cohort 1 (N = 16) and cohort 2 (N = 36). Using simulations based on population PK modeling incorporating cohort 1 data, the following daily dosing regimen was selected for study: 1.5 mg/kg daily from birth through day 7; 3 mg/kg twice daily from days 8–28 of life; and 6 mg/kg twice daily after 4 weeks of age through 6 weeks of age. The geometric mean protocol exposure targets for AUC, Ctrough, and Cmax were met or slightly exceeded in all infants. The chosen neonatal raltegravir dosing regimen was safe and well tolerated in full-term neonates during treatment over the first 6 weeks of life and follow-up to age 24 weeks. Conclusions: Raltegravir can be safely administered to full-term infants using the daily dosing regimen studied. This regimen is not recommended for use in premature infants in a new version of P1110.